The Veiled Women Self-Adjusment - Sofia Panca Kusumawati; Hazim Hazim (Universitas Muhammadiyah Sidoarjo, 2019)
This research aims to find out forms of self-adjustment and factors which underlie the using of veil (cadar). This research uses qualitative method. The research informants in this study are three adult women who are domiciled in Sidoarjo. Determination of the research informants is done by using random sampling. Then, structured interview method is used to collect the data in this research. The result of this research shows that three of informants can perform self-adjustment positively. The positive forms of self-adjustment are be able to face problems directly, be able to solve the problems, be able to do substance (looking for a replacement), be able to understand self-potential, be able to apply learning experience, and be able to act realistic attitude. All of these are supported by the changes of personality and attitude from three informants who grow up more mature and wiser in facing their problems.